A Primer for Assessing the Pathology in Mouse Models of Neuroblastoma. Issue 11 (26th November 2021) - Gifford, Andrew J.; Murray, Jayne; Fletcher, Jamie I.; Marshall, Glenn M.; Norris, Murray D.; Haber, Michelle
Abstract: Neuroblastoma, the most common extracranial solid tumor in young children, arises from the sympathetic nervous system. Our understanding of neuroblastoma has been improved by the development of both genetically engineered and xenograft mouse models of the disease. Anatomical pathology is an essential component of the phenotyping of mouse models of cancer, characterizing the morphologic effects of genetic manipulation and drug treatment. The Th‐MYCN model, the most widely used of several genetically engineered mouse models of neuroblastoma, was established by targeted expression of the human MYCN gene to murine neural crest cells under the control of the rat tyrosine hydroxylase promoter. Neuroblastoma development in Th‐MYCN mice is preceded by neuroblast hyperplasia—the persistence and proliferation of neural crest–derived neuroblasts within the sympathetic autonomic ganglia. The neuroblastomas that subsequently develop morphologically resemble human neuroblastoma and carry chromosomal gains and losses in regions syntenic with those observed in human tumors. In this overview, we describe the essential pathologic features for investigators when assessing mouse models of neuroblastoma. We outline human neuroblastoma as the foundation for understanding the murine disease, followed by details of the murine sympathetic ganglia from which neuroblastoma arises. Sympathetic ganglia, both with and without neuroblast hyperplasia, are described. The macroscopic and microscopic features of murine neuroblastoma are explained, including assessment of xenografts and tumors following drug treatment. An approach to experimental design is also detailed. Increased understanding of the pathology of murine neuroblastoma should improve reproducibility and comparability of research findings and assist investigators working with mouse models of neuroblastoma. © 2021 Wiley Periodicals LLC.